Identification of Cultural Values in the Unjungan Buyut Tradition in Sukamelang: Contextual Learning for Social Studies Learning Resources - Anggun Gumilar; Muhamad Parhan (SAINTIS Publishing, 2025)
The tradition of visiting the ancestors is seen as a cultural heritage that is believed by indigenous people to respect their ancestors. This study focuses on identifying the values contained in the tradition of visiting the ancestors in contextual social studies learning. The method used is a qualitative research method using Roland Barthes' semiotic design. The results of this study indicate that the tradition of visiting the ancestors as a contextual learning resource in social studies subjects is able to increase the values of mutual cooperation, family, togetherness, spirituality, and love of culture. This tradition strengthens intergenerational relationships and has the values of mutual cooperation, family, togetherness, spirituality, and love of culture, making it relevant as a contextual learning resource in social studies.